2012
DOI: 10.1097/ftd.0b013e31827318b8
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Validated Quantification of the Phosphodiesterase Type 5 Inhibitors Sildenafil, Vardenafil, Tadalafil, and 2 of Their Metabolites in Human Blood Plasma by LC-MS/MS─Application to Forensic and Therapeutic Drug Monitoring Cases

Abstract: A liquid chromatography-tandem mass spectrometry assay for the determination of sildenafil, norsildenafil, vardenafil, norvardenafil, and tadalafil in human blood plasma was developed and validated. It has proven to be selective, linear, accurate, and precise for all studied drugs. The method has also proven to be applicable for forensic cases and for therapeutic drug monitoring.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
26
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 33 publications
(28 citation statements)
references
References 20 publications
2
26
0
Order By: Relevance
“…The achieved sensitivity (2 ng on-column) was comparable to those obtained by most LC/MS or LC/MS/MS methods presented in the literature (Tracqui and Ludes, 2003;Eerkes et al, 2002;Rust et al, 2012). Since the coefficient of variation for 10 ng/mL was <20% (CV=18.45%), it was set as the limit of quantification.…”
Section: Lod and Loqsupporting
confidence: 53%
See 1 more Smart Citation
“…The achieved sensitivity (2 ng on-column) was comparable to those obtained by most LC/MS or LC/MS/MS methods presented in the literature (Tracqui and Ludes, 2003;Eerkes et al, 2002;Rust et al, 2012). Since the coefficient of variation for 10 ng/mL was <20% (CV=18.45%), it was set as the limit of quantification.…”
Section: Lod and Loqsupporting
confidence: 53%
“…Several chromatographic techniques have been reported for the determination of sildenafil in plasma samples, such as highperformance liquid chromatography (HPLC) (Guermouche and Bensalah, 2006;Sheu et al, 2003;Lee and Min, 2001;Al-Ghazawi et al, 2007;Cooper et al, 1997;Jeong et al, 2001;Bartošová et al, 2011;Pistos et al, 2008), gas chromatography-mass spectrometry (GC/MS) (Berzas Nevado et al, 2002a), micellar electrokinetic chromatography (MEKC) (Berzas Nevado et al, 2002b), liquid chromatography-mass spectrometry (LC/MS) (Tracqui and Ludes, 2003;Weinmann et al, 2001) and liquid chromatography-tandem mass spectrometry (LC/MS/MS) (Eerkes et al, 2002;Kim et al, 2003;Wang et al, 2005;Rust et al, 2012;Yokoyama et al, 2014). MEKC, LC/MS and LC/MS/MS, although highly sensitive, are expensive and not readily available in most laboratories.…”
Section: Introductionmentioning
confidence: 99%
“…[8,30,34] It allowed simple and fast extraction for screening and quantification of a broad range of drugs by GC-MS and LC-MS. [8,30,34] It allowed simple and fast extraction for screening and quantification of a broad range of drugs by GC-MS and LC-MS.…”
Section: Lle and Gc-ms Analysismentioning
confidence: 99%
“…[17] Lee et al also reported an LC-MS/MS method for the determination of five ED drugs and their selected metabolites in hair to monitor abuse of mirodenafil, sildenafil, tadalafil, udenafil and vardenafil. [18] However, these methods required a relatively long run time, over 5 min, [14][15][16][17][18] which is not suitable for high-throughput tadalafil determination. Thejomoorthy et al reported a sensitive LC-MS/ MS method for tadalafil determination in rat plasma with the linearity range 0.5 to 1,000 ng/ml using liquid-liquid extraction (LLE) method, but it required large amounts of extraction sol-…”
Section: Introductionmentioning
confidence: 99%
“…[11] In recent pharmacokinetic studies, LC-tandem mass spectrometry (LC-MS/MS) has primarily been used for measuring tadalafil in plasma because of its high sensitivity and selectivity. [12][13][14][15][16][17][18][19] Proença et al published a validated ultra-performance liquid chromatography (UPLC)-MS/ MS method for the analysis of sildenafil, vardenafil, and tadalafil in postmortem blood samples. [17] Lee et al also reported an LC-MS/MS method for the determination of five ED drugs and their selected metabolites in hair to monitor abuse of mirodenafil, sildenafil, tadalafil, udenafil and vardenafil.…”
Section: Introductionmentioning
confidence: 99%